The Effect of Economic Stabilization Policies on Economic Growth of Selected ECOWAS Countries - Suleiman Shaku; Olele Hilda Enoh (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2025)
Purpose - This study aims to evaluate the effect of economic stabilization policies on the economic growth of selected ECOWAS countries, particularly focusing on the influence of interest rates, nominal exchange rates, fiscal deficits, and debt stock. Design/methodology/approach - The study employs a panel least squares estimation technique using cross-sectional data from six ECOWAS countries—Nigeria, Ghana, Guinea, Gambia, Sierra Leone, and Liberia—spanning the period from 1990 to 2023. Economic growth, proxied by gross domestic product (GDP), is analyzed against key monetary and fiscal policy variables to determine their impact. Statistical tools including panel unit root test, cointegration test, and the Hausman specification test were employed to ensure robustness. Originality - Unlike previous studies that focus on either fiscal or monetary policies separately or do not consider English-speaking ECOWAS countries in detail, this research provides a holistic analysis of economic stabilization through a combined fiscal-monetary framework. It fills a notable gap by examining the synergies and shortcomings of stabilization policies in the sub-region. Findings and Discussion - The study finds that interest rates, nominal exchange rates, and fiscal deficits have positive and statistically significant effects on economic growth in the selected countries, while debt stock has a negative and significant effect. However, individual country analyses reveal considerable variations: for example, exchange rate had the most significant impact in Nigeria and Guinea, while fiscal deficit drove growth in countries like Liberia and Sierra Leone. The debt burden in most countries counteracts growth gains, revealing risks of overreliance on borrowing. Conclusion - Economic stabilization policies in the ECOWAS sub-region have contributed to economic growth; however, the effectiveness varies across countries and policy tools. While fiscal and monetary measures have shown appreciable influence, rising debt stock threatens long-term sustainability. The study recommends prioritizing internal revenue generation to manage deficits, strengthening policy coordination, and maintaining a balance between growth stimulation and fiscal discipline.